Growth of Epitaxial Anatase Nano Islands on SrTiO3(001) by Dip Coating - Oropeza, F; Zhang, K; Regoutz, A; Lazarov, V; Wermeille, D; Poll, C; Egdell, R (2013)
High temperature annealing of ultrathin anatase-TiO2(001) thin films deposited on SrTiO3(001) substrates by a dip coating method leads to the self-assembly of an array of square-shaped epitaxial anatase islands with lateral dimensions of order 150 nm. The procedure developed here provides a very cheap and simple approach to preparation of oriented anatase nanocrystals with a distribution of surface terminations very different to that found in free-standing material. In particular, the {101} facets which are dominant for unsupported nanocrystalline anatase are completely absent, and the (001) islands are instead bounded by sloping {103} side facets. © 2013 American Chemical Society.